Use of Lactoperoxidase Inhibitory Effects to Extend the Shelf Life of Meat and Meat Products - Beňo, Filip; Velková, Adéla; Hruška, Filip; Ševčík, Rudolf (Microorganisms, 2024)
Lactoperoxidase (LP) is an important enzyme of the salivary and mammary glands. It has been proven to increase the shelf life of raw milk by inhibiting the growth of bacteria, especially Listeria monocytogenes, Escherichia coli, Staphylococcus aureus, and Pseudomonas spp. The aim of this work was to verify the use of LP to extend the shelf life of meat products. In vitro experiments showed inhibitory effects on the selected bacteria (Listeria innocua (ATCC 33090), Staphylococcus saprophyticus (CP054440.1), and Pseudomonas fluorescens (ATCC 13525) due to a prolongation of the lag phase of growth curves. A lower increase in viable counts (p < 0.05) was also found by testing pork cubes' surface treated with LP solution (5%) + L. innocua and stored for 7 days at 15 °C. LP has also been studied at concentrations of 0.25 and 0.50% in meat products (pork ham and pâté) during refrigerated storage (4 °C for 28 days). Lower viable counts were observed throughout the storage experiment, especially for 0.50% LP (p < 0.05). Meat products containing LP also showed lower levels of oxidation (MAD) (p < 0.05). According to these results, LP could extend the shelf life of a wider range of products.
Keywords: meat products; lactoperoxidase; Pseudomonas fluorescens; Listeria innocua; TBARS; Staphylococcus saprophyticus